Warisan Keimanan dan Kesetiaan: Penerapan Pendidikan Agama Kristen oleh Orang Tua di Masa Pandemi Covid-19 - Max Lucky Tinenti; B. D. Nainggolan; Stimson Hutagalung; Rolyana Ferinia (Angelion: Jurnal Teologi dan Pendidikan Kristen, 2021)
The purpose of this study was to examine the role of parents in maintaining the legacy of their children's faith and loyalty, through the existence of Christian religious education in the midst of the covid-19 pandemic restriction situation. Parents need to grow their children's loyalty and faith in the midst of the current covid-19 pandemi situation, so that children can still feel God's presence through their form of faith and loyalty, even though they have to worship at their respective homes. The research method used is a qualitative method with a literature review approach. The data sources are books, journals, Bibles, commentaries, and other sources that can be justified academically. From the results of this study, Christian religious education has a major contribution through the role of parents in maintaining children's faith and loyalty while limiting worship activities during the covid-19 pandemic by implementing PAK through morning and evening worship at home, reading God's Word using detailed methods. and skimming, meditation, and praying individually, in groups, as well as providing spiritual learning through online media